Análisis de la implementación de los responsables de la facturación electrónica en los consultorios privados odontológicos en la ciudad de Tunja-Boyacá (2023)
This work takes electronic billing as its main topic, its objective was to analyze compliance with electronic billing in dental offices in the city of Tunja, taking into account the legal precepts defined in article 15 of law 1966 of 2019, where health service providers are required to generate electronic invoices for payment of health services and technologies.